Turning Waste into Value: A Conceptual AI Supported Model to Promote Circular Economy Participation in Vaasa and Its Potential for International Application. - Fernando, Supuni (My University, 2026)
This research examines the role of AI-based, incentive-enabled digital solutions in supporting participation in municipal waste management and circular economy (CE) activities, particularly for immigrants and the long-term unemployed in Vaasa, Finland. Although the municipality has advanced waste management systems, participation is unequal and reveals structural barriers to engagement. A qualitative case study methodology was utilized, based on semi-structured interviews with institutional stakeholders in the fields of waste management, regional development, and the circular economy (CE). The results show that the barriers to participation are primarily structural rather than motivational and include issues with the flow of communication, the accessibility of information, the limited availability of engaging and adaptive digital solutions, and the fragmentation across the CE ecosystem. Using the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB), the study outlines a conceptual AI-supported engagement model focusing on multilingual digital facilitation, behavioral incentives, and ecosystem coordination. Although the model has not been empirically tested, it provides a framework to show how digital tools can increase the perceived benefits, ease of use, and behavioral control of the user, and in this way, can promote greater participation. The research contributes to CE scholarship by emphasizing inclusive participation and the integration of behavioral and technological perspectives. Although context-specific, the results imply potential relevance for other urban areas experiencing similar participation issues.
Keywords: waste management; circular economy; participation; Sustainable Development Goals; digitalisation; social inclusion; municipal waste; sorting of waste; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business